Hardness and Wear Resistance of ZrO2 Nano Particle Reinforced Al Nanocomposites Produced by Powder Metallurgy. (2015) - Ramachandra, M.; Abhishek, A.; Siddeshwar, P.; Bharathi, V.
Abstract: Nano particle reinforced Aluminium Nanocomposites are produced using Zirconium dioxide (n-ZrO2 ). Nano particles produced by solution combustion method. Urea is used as fuel and then reinforcing into Aluminium matrix in different percentages by weight using the powder metallurgy technique. The specimens prepared are tested for their hardness and microstructure. The above mentioned properties were chosen due to the reinforcement added (n-ZrO2 ) which is known to have good toughness and hardness among other structural properties at room temperature. The composites are tested for wear resistance by using pin on disc wear testing machine. Study of Wear mechanisms, Microstructure were performed on sintered specimens. Microstructure revealed near uniform distribution of n-ZrO2 particles with slight agglomeration. The microstructure also revealed good interfacial bond between matrix and n-ZrO2 particles. Incorporation of n-ZrO2 particles in aluminium matrix can lead to the production of aluminium composites with improved hardness and wear resistance. These composites can find applications in automotive components like pistons, cylinder liners and connecting rods.